Efficacy and safety of a new human fibrinogen concentrate in patients with congenital fibrinogen deficiency: an interim analysis of a Phase III trial. Issue 2 (30th November 2017) - Lissitchkov, Toshko; Madan, Bella; Djambas Khayat, Claudia; Zozulya, Nadezhda; Ross, Cecil; Karimi, Mehran; Kavakli, Kaan; De Angulo, Guillermo R.; Almomen, Abdulkareem; Schwartz, Bruce A.; Solomon, Cristina; Knaub, Sigurd; et al.
Abstract : BACKGROUND: Fibrinogen concentrate is the preferred choice for fibrinogen replacement in congenital fibrinogen deficiency. This study investigated hemostatic efficacy of a new plasma‐derived, double virus‐inactivated (using two dedicated virus inactivation/elimination steps) human fibrinogen concentrate for on‐demand treatment of bleeding episodes (BEs) and surgical prophylaxis. STUDY DESIGN AND METHODS: In this planned interim analysis of a prospective, multinational Phase III study (NCT02267226), 13 patients with afibrinogenemia (≥12 years) received fibrinogen concentrate (FIBRYGA, Octapharma AG). Hemostatic efficacy was assessed by investigators and an independent data monitoring and endpoint adjudication committee (IDMEAC) using objective four‐point criteria and by thromboelastometry maximum clot firmness (MCF). RESULTS: Fibrinogen concentrate was used on‐demand to treat 23 BEs in 11 patients, with 21 (91.3%) requiring a single infusion only. Treatment success was 95.7% (90% confidence interval [CI], 0.81‐1.00; assessment missing for one BE) by investigators and 100% (90% CI, 0.88‐1.00) by IDMEAC. Mean MCF increased significantly from 0.0 to 6.5 mm (95% CI, 5.65‐7.40; p < 0.0001) at 1 hour postinfusion of a median (range) dose of 58.8 (33.9‐101.7) mg/kg per BE. Four patients received fibrinogen concentrate as surgical prophylaxis, with intraoperative and postoperative treatment success rated 100% (90% CI, 0.50‐1.00) by investigators and IDMEAC (median [range] dose per surgery 93.5 [34.1‐225.4] mg/kg). No additional hemostatic interventions were required. No deaths, thromboses, or seroconversions were reported. CONCLUSION: These data showed that the new fibrinogen concentrate was efficacious for on‐demand treatment of acute bleeding and surgical prophylaxis in congenital afibrinogenemia patients.